Conversation: the history of science and the ‘big picture’ - Andrew Barry; J.R.R. Christie; Andrew Cunningham; Ludmilla Jordanova; James Poskett; James A. Secord; Perry Williams; James Poskett (BJHS Themes)
This conversation article brings together six of the original contributors to the 1993 Getting the Big Picture special issue of the British Journal for the History of Science. The contributors introduce their personal memories of the 1991 conference panel which formed the basis of that special issue. They also discuss the wider intellectual, institutional and political contexts of writing the history of science during the 1980s and 1990s, before concluding with reflections on the future of the discipline. The conversation was held live online via Microsoft Teams in March 2023. A professional transcript was produced by Sarah King. The transcript was then edited by James Poskett for length and clarity, before final edits were made by the contributors.